Mapping of Public Space for Cultural Celebration Chinese Ethnic in Chinatown Semarang - Rina Kurniati; Sugiono Soetomo; Imam Buchori (Department of Urban and Regional Planning, Diponegoro University, 2020)
Chinatown, often called Chinezen Wijk, is one of the centers of the city's economic activity. This area is developing very fast, plus the characteristics of worship activities and cultural celebrations that use public space in the form of roads, so that the area becomes crowded. Based on these problems, this study aimed to map the celebration of Chinese ethnic culture in the public space of the Semarang Chinatown. The research method is quantitative descriptive with GIS to map cultural celebration activities in the public space. The analysis results show that cultural celebration activities in the public space are influenced by the duration of the event, location selection, smooth traffic, parking conditions, and road conditions. The results of this study are expected to contribute to better spatial planning policy.